New records of Gerrhonotus parvus Knight & Scudday, 1985 (Squamata, Anguidae) in the state of Coahuila, México - Banda Leal, Javier; Lazcano, David; Barriga Vallejo, Carlos; Nevárez de los Reyes, Manuel (2018)
Abstract We document the first records of Gerrhonotus parvus in the state of Coahuila, México. From March 2012 to March 2017, 6 males and 2 females were found in pine forest and submontane scrubland plant communities in the Sierra de Zapalinamé Natural Protected Area, which is located in the municipalities of Saltillo and Arteaga. These records extend the known distribution of the species 28–44 km west of the nearest occurrences in the state of Nuevo León. Key words Sierra Madre Oriental; submontane scrubland; pine forest; new records; Gerrhonotus parvus; Pygmy Alligator Lizard.